Big Data Analytics and local government: considerations about a process model focused on management - Robert Soares, Jean (2023)
The paper analyzes the aspects that should be considered when proposing a model of Big Data Analytics (BDA) processes in local government with a focus on management. We sought to: carry out a systematic review of the literature to identify the main works aligned with the theme; analyze the trend of BDA use in local governments through the synthesis of publications; and propose, through the key points identified in the analyzed publications, a model of big data analytics processes in local government with a focus on management. The methodological trajectory is defined by a qualitative approach with an exploratory and descriptive objective. To answer the question that guides the conceptual fragment of the study, we chose to carry out a systematic review of the literature. Among the standardized procedures, the Prisma`s model was chosen. The sources of information were some of the main electronic databases in the fields of applied social sciences, focused on administration and public administration, including Web of Science, Scopus, Ebsco and Emerald. A promising trend was noticed in the use of BDA in local governments, with several application cases and a very clear emphasis on its still unexplored potential to offer or transform the relationship between local governments and their citizens. It is concluded that democratic processes can be substantially improved with data-oriented policies, but several factors need to be carefully analyzed and discussed so that the use of opportunities derived from BDA is effectively greater than their possible investment costs and implementation risks.